Pendidikan Karakter Inspirasi Surat Al Fatihah di SPS Bening Bogor - Syafrin, Nirwan; Sumarti (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2024)
This study aims to describe the implementation of character education in SPS Bening Bogor. The implementation is seen from several components, namely: 1) the vision and mission of the institution, 2) learning tools, 3) the involvement of parents in learning and 4) the implementation of learning during distance learning (PJJ). The research uses a qualitative approach. Researchers conducted a study of documents and matching with laapangan. The results of the research found are: 1) the vision and mission of the institution has a distinctive civilized, courageous and inspiring work from the letter al-Fatihah, 2) learning devices are poured in the form of learning programs and its implementation using 4 syntax, 3) parents are involved in character education in the form of religiosity character, in the form of the implementation of worship and adab, 4) during the pandemic learning is carried out with a limited open gaze in accordance with the area , online and parental assignments.